2017
DOI: 10.4103/jfmpc.jfmpc_408_16
|View full text |Cite
|
Sign up to set email alerts
|

Fatal carbon monoxide poisoning: A lesson from a retrospective study at All India Institute of Medical Sciences, New Delhi

Abstract: Background:Carbon monoxide (CO) is a colorless, odorless, tasteless, and nonirritating gas which makes it difficult for those who are exposed, to detect it, leading to unexpected death. This study was undertaken to see the pattern of fatal CO poisoning and to discuss preventive aspect.Materials and Methods:It was a retrospective descriptive study of fatal CO cases which were autopsied at All India Institute of Medical Sciences, New Delhi, from the year 2010 to the year 2015. The cases were analyzed as per age … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(3 citation statements)
references
References 17 publications
(27 reference statements)
1
2
0
Order By: Relevance
“…Similarly, Huang et al (2017) reported high incidence of acute carbon monoxide (CO) poisoning among middle age patients. The reported predominance of males over females in the current study coincided with the findings observed by others studies (Shokrzadeh et al, 2013;Aldossary et al, 2015;Sikary et al, 2017). Meanwhile, it was contrary to the results of a study conducted in Morocco by Rebgui et al (2013) who recorded higher incidence of CO poisoning in females.…”
Section: Discussionsupporting
confidence: 82%
“…Similarly, Huang et al (2017) reported high incidence of acute carbon monoxide (CO) poisoning among middle age patients. The reported predominance of males over females in the current study coincided with the findings observed by others studies (Shokrzadeh et al, 2013;Aldossary et al, 2015;Sikary et al, 2017). Meanwhile, it was contrary to the results of a study conducted in Morocco by Rebgui et al (2013) who recorded higher incidence of CO poisoning in females.…”
Section: Discussionsupporting
confidence: 82%
“…In rural and semi-urban India, there is frequent use of indoor coal-burning heaters and stoves during winter months. Practices of using wood and other indigenous forms of cooking equipment are also not uncommon giving rise to increased CO emissions (Sikary et al, 2017).…”
Section: Research Articlementioning
confidence: 99%
“…[3]. Due to its properties, it is often difficult to detect the presence of CO, describing it as a 'silent killer' [4]. The inhalation of CO can deprive the capacity of blood to carry oxygen and combines with hemoglobin to form carboxyhemoglobin [5].…”
Section: Introductionmentioning
confidence: 99%